How to Overcome the Antibiotic Crisis Facts, Challenges, Technologies and Future Perspectives - Stadler, Marc; Dersch, Petra (Current Topics in Microbiology and Immunology, 2016)
This volume focuses on antibiotics research, a field of topical significance for human health due to the worrying increase of nosocomial infections caused by multi-resistant bacteria. It covers several basic aspects, such as the evolution of antibiotic resistance and the influence of antibiotics on the gut microbiota, and addresses the search for novel pathogenicity blockers as well as historical aspects of antibiotics. Further topics include applied aspects, such as drug discovery based on biodiversity and genome mining, optimization of lead structures by medicinal chemistry, total synthesis and drug delivery technologies. Moreover, the development of vaccines as a valid alternative therapeutic approach is outlined, while the importance of epidemiological studies on important bacterial pathogens, the problems arising from the excessive use of antibiotics in animal breeding, and the development of innovative technologies for diagnosing the "bad bugs" are discussed in detail. Accordingly, the book will appeal to researchers and clinicians alike.